Implementation of process management to increase effiiciency in a Peruvian transport company - Roncal Marin, Estefanny Yadhira; Aranda Cárdenas, Thalia Zarali; Escurra Lagos, Jean Carlos (LACCEI, 2025)
The objective of this research was to implement process management to increase the efficiency of support processes in a transportation company. Its importance lies in applying process management as a key approach to improve organizational efficiency. The study was applied, with a quantitative approach, explanatory level and pre-experimental design, evaluating the efficiency before and after the implementation in the support processes. Techniques such as observation, documentary analysis, process maps and cause-effect diagrams were used, as well as statistical and modeling tools. Having a 30-day sample, the Shapiro Wilk normality test was used, where a p-value >0.05 was obtained. The results showed a significant increase in the efficiency of all the support processes analyzed, with an increase of 23%, validated by T-Student and Wilcoxon tests (p < 0.001), concluding that process management allowed to increase the efficiency of the support processes by optimizing resources, reducing operating times and costs, improving the quality of service and strengthening the competitiveness of the company in the transportation sector.